When Health Trumps Money: Economic Incentives and Health Equity in the Provision of Nursing Homes - Øystein Hernæs; Snorre Kverndokk; Simen Markussen; Henning Øien (Center for Economic Studies and ifo Institute (CESifo), 2023)
The allocation of public care services should be determined by individual needs but can be influenced by economic factors. This paper examines the impact of economic incentives on the allocation of nursing home care in the Norwegian long-term care system. The study uses a theoretical model and empirical data from the municipality of Oslo to determine if nursing home spots are allocated based on income, which would be financially advantageous for the provider. We do not find evidence that the economic incentives of the care provider play a role in the allocation of nursing homes. Thus, in this setting, needs seems to be the dominant factor for allocation of nursing home care, while economic incentives seem to play no significant role.
Keywords: I14; I18; H51; 330; long-term care; economic incentives in health care; health care equity